(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
The aim of this article reports results of the study that examined the experiences of the practitioners in Namibian Higher Education institutions on the implementation of Education for Sustainable Development. Although the article demonstrated that lecturers in the Namibian Higher Education Institutions view education for sustainable development as cross-cutting discipline that should be the responsibility of all lecturers, it seems that lecturers do not teach it collaboratively, as required by international bodies. The members of institutions’ management should inspire and motivate the idea of sustainability and environmental awareness, and actively promote the transformation of society through the adoption of a policy and action plan on education for sustainable development.